ANALISIS YURIDIS AKTA KETERANGAN WARIS YANG DIBUAT OLEH NOTARIS DALAM KETENTUAN PEMBUATAN AKTA OTENTIK BERDASARKAN UUJN NO. 2 TAHUN 2014 - MIA IRIANDINI (PREMISE LAW JURNAL, 2016)
The result of this study showed that the authority of Notary to make and issue the Letter of Certification of Inheritance is not regulated in detail because this is only the habitual activity of the previous Notaries which is then followed by the next and current Notaries. Basides, based on the habitual action, in the making of the Letter of Certification of Inheritance, Notaries also refer to the Circular Letter of Legal Development Board, Directorate General of Agraria, Department of Domestic Affairs No: 44DP/12/63/12/69 dated December 20, 1969 on Letter of Certification of Inheritance and the Evidence of Citizenship as their legal base. It is regulated that for the Indonesian citizen of the indigeneous people origin, the Certification of Inheritance is made by the heir(s) witnessed by 2 (two) witnesses which is then approved and certified by Lurah (Head of Urban Village) and Camat (Head of Subdistrict). For the Indonesia Citizen of foreign eastern descent origin, the Certification of Inheritance should be obtained from BalaiHartaPeninggalan (the Office of Inheritance Affairs). The categorization of population and the existing law for every category of population should have been eliminated. The practice of this stipulation is regarded as a discriminative action as well as rasialism and of course it is on the contrary with the principles of human rights. So, this kind of regulation stuipulation must be ended immediately by determining the authority of Notary as the only official who makes and issues the Certification of Inheritance and regulated in the the UUJN (Law on Notary’s Position).